(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the state of development of the digital economy in the Republic of Uzbekistan, existing opportunities and existing problems. The emergence of professions based on digital technologies in the future, as well as the growth dynamics of the volume of services in the field of "information and communication" in gross value added in Uzbekistan, are shown. Also, proposals and recommendations were developed on the adopted strategic documents, state programs, and statistical data on the dynamics of their implementation in the digital economy.